A novel and high-efficiency dual-electron gun concurrent preheating additive manufacturing technology: suppressing thermal cracks in non-weldable IN738LC nickel-based superalloy by mitigating temperature fluctuations - Yang Li; Hongyu Long; Yurong Wang; Bo Wei; Yuemei Tan; Jun Zhou; Xiaoyu Liang; Lei Zhang; Feng Lin (Virtual and Physical Prototyping)
The process of electron beam powder bed fusion (PBF-EB) is recognised for its efficacy in preparing non-weldable nickel-based superalloys, leveraging high-temperature preheating to minimise stress-related issues. Traditionally, the PBF-EB process involves pausing the preheating scan during printing phases when only one electron gun is available, leading to significant temperature fluctuations and hot cracking during the solidification of these alloys. To address the challenge of fabricating complex parts from such materials, a novel concurrent preheating electron beam powder bed fusion (CPPBF-EB) process employing dual-electron guns has been introduced. An in-depth analysis was conducted on the crack mechanisms of PBF-EBed nickel-based superalloys. Thermal oscillations inherent to the conventional electron beam powder bed fusion (CVPBF-EB) process synergistically induce three pivotal mechanisms in IN738LC superalloys: non-equilibrium carbide precipitation, destabilisation of the γ′ strengthening phase, and stress-mediated dislocation accumulation. These coupled phenomena arise from dynamic thermal gradients during cyclic reheating, which amplify interfacial stress concentrations and enable dislocation penetration through γ′ precipitates, ultimately initiating microcrack formation at geometric heterogeneities. Crucially, we demonstrate that implementing secondary electron beam thermal stabilisation effectively suppresses deleterious phase evolution and defect generation. This breakthrough highlights thermal field modulation as a pivotal control parameter for defect-resistant additive manufacturing of precipitation-strengthened alloys.